TINJAUAN YURIDIS KEDUDUKAN PENANGGUNG/BORGTOCHT DALAM PERKARA KEPAILITAN DAN PKPU TERHADAP UTANG DEBITOR - Rosalia Hidayat (Fakultas Hukum Universitas Kristen Indonesia, 2021)
A loan agreement between the parties may result in default. The provision of guarantees is very necessary in an effort to minimize default. The form of guarantee consists of material guarantee (material) and immaterial guarantee (individual). Material guarantees can be in the form of a mortgage, mortgage, mortgage, and fiduciary security, while individual guarantees are in the form of a guarantor (borgtocht), liability, and a guarantee agreement. The existence of a debt guarantor, namely a third party as guarantor (borgtocht), where as a debtor's debt guarantor when the debtor does not meet his performance. When the Debtor experiences Bankruptcy or PKPU due to the debtor defaulting or unable to pay his debt, the creditor immediately asks for responsibility for Borgtocht as the guarantor without any debt collection from the debtor. Often the creditor immediately collects the debt from the guarantor, who is clearly not a debtor. And this happens in the bankruptcy law and PKPU, namely the guarantor of the bankruptcy debtor by the creditor without first seeing the debtor's real assets. Keywords: borgtocht, bankruptcy and debtor